2019
DOI: 10.1002/cbin.11154
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CXCL16 promotes TNF‐α‐induced apoptosis in DLBCL via the AMAD10‐NF‐κB regulatory feedback loop

Abstract: We had previously identified that the co‐expression of transmembrane CXCL16 (TM‐CXCL16) and its receptor CXCR6 is an independent risk factor for poor survival in patients with diffuse large B‐cell lymphoma (DLBCL). However, the impact of the soluble form of CXCL16 (sCXCL16) on the pathogenesis of DLBCL remains unknown. In the present study, the synergistic effect of sCXCL16 and tumor necrosis factor α (TNF‐α) on apoptosis in DLBCL cell lines (OCI‐LY8 and OCI‐LY10) was investigated in vitro. sCXCL16 reinforced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…In a positive feedback loop, sCXC16 secretion promoted TNF- α production via the NF- κ B signalling pathway in DLBCL cells (Ref. 22). In addition to TNF- α , it has also been shown that IFN- γ stimulated CXCL16 production from tumour cells in prostate cancer (Ref.…”
Section: Cxcl16 Expression In Cancermentioning
confidence: 99%
“…In a positive feedback loop, sCXC16 secretion promoted TNF- α production via the NF- κ B signalling pathway in DLBCL cells (Ref. 22). In addition to TNF- α , it has also been shown that IFN- γ stimulated CXCL16 production from tumour cells in prostate cancer (Ref.…”
Section: Cxcl16 Expression In Cancermentioning
confidence: 99%
“…The complex environment of DLBCL possesses TNF-α along with chemokines and some cytokines produced in mesenchymal matrix from different inflammatory cells. In a recent study, it has been proved that sCXCL16 can reinforce TNF-α to mediate the DLBCL cell proliferation [34]. In this process, NF-κB signaling is activated by sCXCL16 to increase the production of TNF-α in DLBCL cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with previous studies that demonstrated the capacity of CXCL16 to induce VEGF in human umbilical vein endothelial cells ( 38 , 39 ) and tumor cells ( 41 ). In addition, CXCL16 binding to its receptor CXCR6 induced upregulation of phospho-ERK1/2 in human umbilical vein endothelial cells ( 38 , 39 ) and activated the pro-inflammatory transcription factor NF-κB signaling pathway ( 68 ). These results suggest that one possible mechanism of CXCL16-induced pathological neovascularization in PDR is related to the upregulation of VEGF.…”
Section: Discussionmentioning
confidence: 99%